AN ENERGY-ADAPTIVE MULTIPLE PATHS ROUTING APPROACH FOR WIRELESS SENSOR NETWORKS - SHI, JINGLUN; CAI, KANG; HE, CHENGHONG; WEI, GANG; SHAN, ZHILONG (Journal of Mobile Multimedia, 2012)
A wireless sensor network (WSN) is expected to have a significant impact on military and civil applications such as target field imaging, intrusion detection, weather monitoring. Sensors are battery-powered, and hence energy-conserving communications are essential to prolong the sensor network’s lifetime. Also, given the unreliable nature of the wireless channels and the high failure rate of the individual sensors, a fault tolerant routing protocol with energy-efficiency is getting more and more attention. In this paper, we propose an energy-adaptive multiple paths routing algorithm (EMRA) for wireless sensor networks. It consists of three elements: (i) gradients to disseminate data over multiple paths from a source to a sink, (ii) rules used for setting up disjoint multiple paths, and (iii) policies for selecting multiple paths. By limiting the maximum number of the gradients, the exploratory data messages forwarded is decreased efficiently. By using the rules for setting up disjoint multiple paths, the sink node can get a sufficient number of disjoint multiple paths, which enables EMRA to recover from a routing failure quickly. Our analysis and simulation results reveal that EMRA performs better than the existing multiple paths routing algorithms in terms of the average dissipated energy and the delay to set up multiple paths.